The Role of Connectedness and Psychological Hardiness in EFL Teachers’ Pedagogical Effectiveness - Liu, Zhenzhen (Frontiers in Psychology, 2022)
The role of emotions in EFL teachers’ pedagogical success and efficacy has long been emphasized in the literature. However, the power and impact of teachers’ positive psycho-emotional factors like sense of connectedness and hardiness have been marginally explored in EFL contexts. Against this shortcoming, the present mini-review article made an attempt to provide the theoretical and research underpinnings of three prominent teacher-related factors, namely, connectedness, psychological hardiness, and pedagogical effectiveness as well as their interplay. Moreover, the research trends, gaps, and future directions are provided for enthusiastic researchers. Finally, some practical implications for EFL teachers, teacher trainers, and SLA researchers are offered to raise their awareness of psycho-emotional factors in second/foreign language education.